Seroprevalence of Melioidosis among cattle in Foster Farm Programme of the Faculty of Veterinary Medicine, Universiti Putra Malaysia - Abd Kadir, Muhamad Syazrin (2017)
In the endeavour to advance Malaysia into a ‘halal’ hub the livestock animals should be free from infectious disease. Melioidosis is endemic in South-East Asia and northern Australia. The disease is also a significant animal health that reduces the productivity of animals and loss of valuable animal protein. A previousstudy on the seroprevalence of Melioidosis in livestock animals in 2000-2009 was carried out by the Department of Veterinary Services Malaysia indicate evidence of 100,262 animals tested, a total of 5,729 (5.7%) were positive for Melioidosis. Since then there was no follow-up study. This study focuses on seroprevalence of Melioidosis in Foster Farm Programme of FPV, UPM. Fifty cattle with mix-age and gender were selected randomly for blood sample collection from the Foster Farm Programme of FPV, UPM. Complement Fixation Test (CFT) was used to detect antibody against melioidosis. The result from CFT showed negative for all samples obtained from Foster Farm Programme FPV, UPM. The lack of positive case probably due to small sample number and also related to the management practices where the cattle mostly kept under a semi-intensive system in which they had less contact with soil and therefore at a lower risk of contracting the organism. This indicates there is zero seroprevalence in Foster Farm Programme FPV, UPM, which is free of Melioidosis.